A method for improving electron transfer efficiency at the interface of tin dioxide-lead halide perovskite
By using L-aspartate solution spin coating and treatment technology on the interface under the lead halide perovskite solar cells, efficient passivation of the SnO2/lead halide perovskite interface was successfully achieved, solving the problem of dissolution of passivation materials in the prior art, and improving electron transmission efficiency and photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202111537997.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-12-15
AI Technical Summary
In the prior art, in the process of passivating the interface under the lead halide perovskite solar cell, the passivation material is easily dissolved by the perovskite precursor solvent, resulting in a significant reduction in the passivation effect of the interface.
The L-aspartate solution was spin-coated on the conductive glass substrate of SnO2 electron transport material, and through heat treatment and ultraviolet ozone cleaning, the L-aspartate molecules were successfully placed at the interface of SnO2/lead halide perovskite film to achieve efficient passivation.
By efficiently passivating interface defects, the electronic transmission efficiency of SnO2/lead halide perovskite interface is significantly improved, and thus the photoelectric conversion efficiency of solar cells is improved.
Smart Images

Figure HDA0003413112230000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaic device preparation, and specifically relates to a method for improving the electron transmission efficiency at the tin dioxide-lead halide perovskite interface. Background Art
[0002] After rapid development in recent years, the laboratory energy conversion efficiency of perovskite photovoltaic cells based on lead halide perovskite materials has exceeded 25%, attracting the attention of researchers and industry from all over the world. Perovskite solar cells are composed of transparent conductive glass electrodes, electron transport layers, lead halide perovskite light absorption layers, hole transport layers and metal counter electrodes. During the operation of the battery, the lead halide perovskite material absorbs sunlight and conducts electrons and holes to the electron transport material and hole transport material at the interface with the electron transport layer and the hole transport layer, completing the physical space separation of photogenerated electron-hole pairs. Studies have shown that the interface properties of lead halide perovskite materials and electron / hole transport materials directly affect the separation efficiency of photogenerated carriers, thereby affecting the photoelectric conversion performance of the device. In addition, the above two interface properties also play a key role in the stability of the battery, which makes the optimization of the interface between lead halide perovskite materials and electron / hole transport materials the key to improving the overall performance of the device. In the preparation of positive structure perovskite solar cells, a layer of passivation material is usually spin-coated on the electron transport layer to passivate the interface defects of the electron transport layer / lead halide perovskite. However, this method of treating the lower interface has the following problems: Since these methods modify the passivation material on the surface of oxide films such as TiO2 and SnO2, in the subsequent preparation process of lead halide perovskite films, these passivation materials are easily dissolved by the perovskite precursor solvent and deviate from the interface, resulting in a significant decrease in the passivation effect of the interface. Therefore, it is of great significance to develop a new method for passivation of the lower interface of positive structure perovskite solar cells, further optimize the interface performance of lead halide perovskite materials and electron transport materials, and thus improve the transmission efficiency of photogenerated electrons at the lower interface, which is of great significance to the performance improvement of this structure perovskite solar cell. Summary of the invention
[0003] In view of the problems existing in the optimization of the lower interface performance of the existing lead halide perovskite solar cells, the purpose of the present invention is to provide a method for improving the electron transmission efficiency of the tin dioxide-lead halide perovskite interface. In the SnO2 / lead halide perovskite film and photovoltaic device prepared by this method, the L-aspartic acid passivation material is successfully placed at the lower interface of the device (i.e., the SnO2 / lead halide perovskite film interface), achieving efficient passivation of the interface defects of the SnO2 electron transmission material / lead halide perovskite material, thereby improving the interface electron transmission efficiency, and the photoelectric conversion efficiency of the battery is also improved.
[0004] The technical solution of the present invention is:
[0005] A method for improving the electron transmission efficiency of a tin dioxide-lead halide perovskite interface comprises the following steps:
[0006] (1) Preparation of L-aspartate solution: dissolving L-aspartate in deionized water and stirring at room temperature for 0.5 to 2 hours to obtain an L-aspartate solution; wherein the molar concentration of the L-aspartate is between 0.05 and 0.5 M;
[0007] (2) Preparation of L-aspartate-SnO2 thin film: The L-aspartate solution obtained in step (1) is spin-coated on a conductive glass substrate containing SnO2 electron transport material, the spin coater speed is 2000-4000 rpm, and the spin coating time is 20-60 seconds; after the spin coating is completed, the obtained substrate is heated at 100-200° C. for 10-30 minutes to obtain an L-aspartate-SnO2 thin film substrate;
[0008] (3) Treatment of L-aspartate-SnO2 thin film substrate: placing the L-aspartate-SnO2 thin film substrate obtained in step (2) in a UV-ozone cleaning machine for 10 to 30 minutes;
[0009] (4) Passivation of SnO2 / lead halide perovskite interface: The lead halide perovskite precursor solution is added dropwise onto the thin film substrate obtained in step (3) and immersed for 5 to 10 seconds. Then, the spin coater is started and a reverse polarity solvent is added dropwise. After the spin coating is completed, the obtained substrate is placed on a heating table for heat treatment to prepare a lead halide perovskite thin film.
[0010] The method for improving the electron transfer efficiency at the tin dioxide-lead halide perovskite interface is that since the solubility of L-aspartic acid in the perovskite precursor solution is extremely low, the L-aspartic acid molecules can be stored at the SnO2 / lead halide perovskite interface, passivating the interface defects, thereby improving the electron transfer efficiency at the SnO2 / lead halide perovskite interface.
[0011] The method for improving the electron transport efficiency of the tin dioxide-lead halide perovskite interface, in step (1), when the L-aspartate solution is prepared, the L-aspartate is L-aspartate sodium salt (CAS number: 3792-50-5), L-aspartate sodium salt monohydrate (CAS number: 323194-76-9), L-aspartate monopotassium salt hydrate (CAS number: 1115-63-5), L-aspartate magnesium salt (CAS number: 2068-80-6) or L-aspartate hemimagnesium salt dihydrate (215533-00-9).
[0012] The method for improving the electron transport efficiency of the tin dioxide-lead halide perovskite interface is as follows: L-aspartic acid has low solubility in the lead halide perovskite precursor solution and is retained at the interface between the SnO2 electron transport layer and the lead halide perovskite layer; a Spiro-OMETAD hole transport layer is spin-coated on the perovskite film, and a gold electrode is evaporated to prepare a positive structure perovskite solar cell with a lower interface passivation; the presence of L-aspartic acid molecules on the lower interface of the photovoltaic device improves the interface electron transport efficiency of the SnO2 / lead halide perovskite.
[0013] The design idea of the present invention is:
[0014] Studies have shown that the use of fullerene derivatives such as PCBM, zwitterionic organics and other materials can passivate the lead halide perovskite grain boundaries and the interface defects of the electron transport layer / lead halide perovskite. Most existing methods are based on spin coating a layer of the above passivation materials on the electron transport layer. Affected by the subsequent preparation process of the lead halide perovskite film, these passivation materials are easily dissolved by the perovskite precursor solution and deviate from the interface, resulting in a decrease in the interface passivation effect. This study found that the solubility of L-aspartic acid in the perovskite precursor solution is extremely low, but L-aspartate is soluble in water. On the other hand, the carboxyl group of L-aspartic acid can passivate the oxygen vacancy defects of the SnO2 film, while the amino group can passivate the iodine defects of the perovskite film. The present invention utilizes these characteristics of the groups carried by L-aspartic acid and its low solubility in the perovskite precursor solution, successfully prepares L-aspartic acid molecules at the interface of SnO2 film / lead halide perovskite, and realizes efficient in-situ passivation of the SnO2 film / lead halide perovskite interface, thereby improving the interface electron transmission efficiency. The positive structure perovskite solar cell prepared by this interface modification method has improved photogenerated electron transmission capacity and improved photoelectric conversion efficiency of the battery.
[0015] The advantages and beneficial effects of the present invention are as follows:
[0016] 1. The method for improving the electron transmission efficiency of the tin dioxide-lead halide perovskite interface developed by the present invention, in which the L-aspartic acid passivation material is successfully placed at the lower interface of the positive structure device, and the interface defects of the SnO2 electron transport layer / lead halide perovskite film are efficiently passivated in situ, thereby greatly improving the transmission efficiency of the interface electrons, and the photoelectric conversion efficiency of the battery is also improved.
[0017] 2. The method for improving the electron transfer efficiency at the tin dioxide-lead halide perovskite interface developed by the present invention is centered on the passivation of SnO2 and lead halide perovskite surface defects by different groups carried by L-aspartic acid, and combined with its low solubility in the perovskite precursor solution, successfully achieved high-efficiency passivation.
[0018] 3. The process of the present invention has low cost, simple operation and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 : Schematic diagram of the L-aspartic acid sodium salt passivated lower interface positive structure perovskite solar cell prepared in Example 1 (a), ToF-SIMS analysis results of the lower interface of the device (b), fluorescence spectrum (c) and photocurrent-voltage curve of the device (d).
[0020] (a) In the figure, Au is gold element, Spiro-OMETAD is hole transport layer (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), Perovskite is lead halide perovskite, L-Aspartic is L-aspartic acid interface passivation layer, SnO2 is tin dioxide, and ITO is indium tin oxide transparent conductive film; (b) In the figure, Perovskite / L-Aspartic / SnO2 Interface is the interface between tin dioxide and lead halide perovskite passivated by L-Aspartic, the horizontal axis Sputtering Time (s) represents the sputtering time (seconds), and the vertical axis Intensity (counts) represents the intensity; (c) In the figure, the horizontal axis Wavelength (nm) represents the wavelength (nanometers), and the vertical axis Intensity (au) represents the intensity; (d) In the figure, the horizontal axis Voltage (V) represents the voltage (volts), and the vertical axis Current Density (mA·cm -2 ) represents the current density (mA / cm2). DETAILED DESCRIPTION
[0021] In a specific implementation process, the present invention disperses L-aspartate in deionized water to prepare an L-aspartate solution; spin-coats the L-aspartate solution on a conductive glass substrate with tin dioxide (SnO2) electron transport material deposited on the surface, and anneals at 100-200° C. for 10-30 minutes to obtain an L-aspartate-SnO2 film; the L-aspartate-SnO2 film is placed in an ultraviolet ozone cleaning machine for 10-30 minutes; a lead halide perovskite precursor solution is dripped on the surface of the film and immersed for 5-10 seconds, then the spin coater is started, and a reverse polarity solvent is dripped. After the spin coating is completed, the substrate is placed on a heating table for heat treatment to prepare a lead halide perovskite film. Due to the extremely low solubility of L-aspartic acid in perovskite precursors, the L-aspartic acid molecules can be preserved at the SnO2 / lead halide perovskite interface, passivating the interface defects and thereby improving the electron transfer efficiency at the SnO2 / lead halide perovskite interface.
[0022] The present invention is further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.
[0023] Example 1
[0024] In this embodiment, the method for improving the electron transmission efficiency of the tin dioxide-lead halide perovskite interface is as follows:
[0025] (1) First, prepare a lead halide perovskite precursor solution by dissolving 742.2 mg of lead iodide (PbI2), 224.4 mg of formamidine iodide (FAI), 16.2 mg of methylamine bromide (MABr), 20.3 mg of methylamine chloride (MACl) and 19.8 mg of cesium iodide (CsI) in 1 mL of a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), wherein the volume ratio of DMF to DMSO in the solvent is 4:1. Stir at room temperature for 2 hours to form a uniform, stable and transparent lead halide perovskite precursor solution.
[0026] (2) Then, a sodium L-aspartate solution was prepared by dissolving 17.3 mg of sodium L-aspartate monohydrate in 1 mL of deionized water and stirring the solution at room temperature for 1 hour to obtain a sodium L-aspartate aqueous solution with a molar concentration of 0.1 M.
[0027] (3) Take 0.2 mL of L-aspartic acid sodium salt aqueous solution and spin coat it on an ITO conductive glass substrate (2 cm×2 cm) containing SnO2 electron transport material. The speed of the spin coater is 3000 rpm and the spin coating time is 25 seconds. After the spin coating is completed, the obtained substrate is heated at 150°C for 10 minutes to obtain an L-aspartic acid sodium-SnO2 thin film substrate.
[0028] (4) Place the sodium L-aspartate-SnO2 thin film substrate in a UV ozone cleaning machine. After 10 minutes of treatment, add the lead halide perovskite precursor solution prepared in step (1) to the surface of the sodium L-aspartate-SnO2 thin film substrate, let it stand for 5 seconds, start the spin coater, spin coat at 4000 rpm for 40 seconds, take 0.5 mL of chlorobenzene solvent, and add it to the surface of the rotating substrate for washing.
[0029] The obtained substrate is then placed on the heating table of a hot plate furnace, baked at 100°C for 10 minutes, and then removed and cooled to room temperature, thereby completing the passivation of the SnO2 / lead halide perovskite interface while preparing the lead halide perovskite film. After that, a Spiro-OMETAD hole transport layer is spin-coated on the perovskite film and a gold electrode is evaporated to prepare a positive-structure perovskite solar cell passivated with L-aspartic acid.
[0030] like Figure 1As shown, a schematic diagram of a positive-structure perovskite solar cell prepared using this process flow, the ToF-SIMS analysis results of the lower interface of the device, the fluorescence spectrum, and the photocurrent-voltage curve of the device.
[0031] like Figure 1 As shown in a, L-aspartic acid is located at the lower interface of the device, namely the SnO2 / lead halide perovskite interface. Figure 1 The ToF-SIMS analysis results shown in b show that the COO at the bottom of the lead halide perovskite layer - The signal shows that the L-aspartic acid molecules are at the SnO2 / lead halide perovskite interface. The fluorescence analysis results show that the fluorescence lifetime of the lead halide perovskite film at the interface passivated by L-aspartic acid is lower than that of the unpassivated film, indicating that L-aspartic acid effectively passivates the interface defects of SnO2 / lead halide perovskite, thereby improving the transmission efficiency of photogenerated electrons at the interface ( Figure 1 c). The photocurrent-voltage curve of the battery under AM 1.5G conditions shows that the photoelectric conversion efficiency of the positive structure perovskite battery passivated with L-aspartic acid is 10% higher than that of the unpassivated device, reaching about 22%, and the hysteresis phenomenon of the battery is reduced ( Figure 1 d), indicating that the lower interface passivated with L-aspartic acid has excellent electron transfer efficiency.
[0032] The results of the embodiment show that due to the extremely low solubility of L-aspartic acid in the lead halide perovskite precursor solution, L-aspartic acid is difficult to be dissolved by the perovskite precursor solution, and thus is retained at the interface between the SnO2 electron transport layer and the lead halide perovskite film, thereby passivating the interface defects. The Spiro-OMETAD hole transport layer is spin-coated on the perovskite film obtained by the above process, and a gold electrode is evaporated to prepare a positive structure perovskite solar cell with a lower interface passivation. In this battery, due to the passivation effect of the L-aspartic acid molecules at the lower interface of the device, the interface electron transmission efficiency is significantly improved, and the photoelectric energy conversion efficiency is increased by more than 10% compared with the unpassivated device.
Claims
1. A method for improving the electron transfer efficiency of tin dioxide-lead halide perovskite interface, characterized in that: The steps include: (1) Preparation of L-aspartate solution: dissolve L-aspartate in deionized water and stir at room temperature for 0.5 to 2 hours to obtain an L-aspartate solution; wherein the molar concentration of L-aspartate is between 0.05 and 0.5 M; (2) Preparation of L-aspartate-SnO2 thin film: Spin-coat the L-aspartate solution obtained in step (1) onto a conductive glass substrate containing SnO2 electron transport material, with the spin coater rotating at 2000-4000 rpm for 20-60 seconds; after the spin coating, heat the obtained substrate at 100-200°C for 10-30 minutes to obtain an L-aspartate-SnO2 thin film substrate; (3) Treatment of L-aspartate-SnO2 thin film substrate: Place the L-aspartate-SnO2 thin film substrate obtained in step (2) in a UV-ozone cleaning machine for 10 to 30 minutes; (4) Passivation of SnO2 / lead halide perovskite interface: The lead halide perovskite precursor solution is dripped onto the thin film substrate obtained in step (3) and immersed for 5 to 10 seconds. Then, the spin coater is started and a reverse polarity solvent is dripped. After the spin coating is completed, the obtained substrate is placed on a heating table for heat treatment to prepare a lead halide perovskite thin film. Due to the extremely low solubility of L-aspartic acid in the perovskite precursor solution, the L-aspartic acid molecules can be preserved at the SnO2 / lead halide perovskite interface, passivating the interface defects and thereby improving the electron transfer efficiency at the SnO2 / lead halide perovskite interface.
2. The method for improving the electron transfer efficiency of the tin dioxide-lead halide perovskite interface according to claim 1, characterized in that: In step (1), when the L-aspartate salt solution is prepared, the L-aspartate salt is L-aspartate sodium salt, L-aspartate sodium salt monohydrate, L-aspartate monopotassium salt hydrate, L-aspartate magnesium salt or L-aspartate hemimagnesium salt dihydrate.
3. The method for improving the electron transfer efficiency of the tin dioxide-lead halide perovskite interface according to claim 1, characterized in that: L-aspartic acid has low solubility in the lead halide perovskite precursor solution and is retained at the interface between the SnO2 electron transport layer and the lead halide perovskite layer. A Spiro-OMETAD hole transport layer is spin-coated on the perovskite film and a gold electrode is evaporated to prepare a positive-structured perovskite solar cell with a passivated lower interface. The presence of L-aspartic acid molecules at the lower interface of the perovskite solar cell improves the interface electron transport efficiency of the SnO2 / lead halide perovskite.
Citation Information
Patent Citations
Interface modification method for eliminating hysteresis phenomenon of perovskite cell
CN108832004A
Perovskite battery, preparation method thereof and preparation method of modification layer of perovskite battery
CN113140679A